2005
DOI: 10.1354/vp.42-5-550
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Differentially Expressed Genes of Primary Tumors in the Canine Central Nervous System

Abstract: Abstract. The pathophysiologic similarities of many human and canine cancers support the role of the domestic dog as a model for brain tumor research. Here we report the construction of a custom canine brainspecific cDNA microarray and the analysis of gene expression patterns of several different types of canine brain tumor. The microarray contained 4000 clones from a canine brain specific cDNA library including 2161 clones that matched known genes or expressed sequence tags (ESTs) and 25 cancer-related genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
2
33
0
6
Order By: Relevance
“…Compared to the total number of genes with preferential expression, we found higher frequencies of proliferation and cell death genes expressed in the brain than retina, and nucleic acid processing genes in retina than brain. Among the transcripts preferentially expressed in the brain were many known and unknown genes not previously reported to have a preferential expression pattern in different regions of the brain [5,29]. We demonstrated also that expression patterns are quite restricted to individual cortex areas, as few differential expressed genes showed overlap between the examined brain regions (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
“…Compared to the total number of genes with preferential expression, we found higher frequencies of proliferation and cell death genes expressed in the brain than retina, and nucleic acid processing genes in retina than brain. Among the transcripts preferentially expressed in the brain were many known and unknown genes not previously reported to have a preferential expression pattern in different regions of the brain [5,29]. We demonstrated also that expression patterns are quite restricted to individual cortex areas, as few differential expressed genes showed overlap between the examined brain regions (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
“…Overexpression of surface markers previously defined in human tumors, suitable for tumor targeting strategies, has been demonstrated for IL‐13RA2, EphA2, and alpha3‐beta1 integrin in a variety of canine brain tumors (Fig 4). 127, 128, 129, 130 To date, global expression studies have utilized relatively limited microarray platforms and have shown some similarities to differentially expressed genes found in human tumors 131. At the epigenetic level, preliminary studies profiling genome‐wide methylation status of canine glioma suggest that hypermethylation patterns in developmentally regulated genes may be similar to those in human gliomas 132…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…For example, canine glioblastomas show immunoreactivity for glial fibrillary acidic protein (11)(12)(13), and epidermal growth factor receptor and vascular endothelial growth factor overexpression has been observed in canine astrocytic tumors, as has p53 deregulation (11,13). Finally, microarray analysis indicates similar patterns of differentially expressed genes in canine and human brain tumors (14). Chemo-and radiosensitivity similarities are less well documented.…”
Section: Translational Models Companion Animals and Brain Cancermentioning
confidence: 99%